Trypanosomes lack a canonical EJC but possess an UPF1 dependent NMD-like pathway - Bernardo Papini Gabiatti; Eden Ribeiro Freire; Johanna Odenwald; Janaina de Freitas Nascimento; Fabiola Holetz; Mark Carrington; Susanne Kramer; Martin Zoltner (PLoS ONE, 2025)
The exon junction complex (EJC) is a key player in metazoan mRNA quality control and is placed upstream of the exon-exon junction after splicing. Its inner core is composed of Magoh, Y14, eIF4AIII and BTZ and the outer core of proteins involved in mRNA splicing (CWC22), export (Yra1), translation (PYM) and nonsense mediated decay (NMD, UPF1/2/3). Trypanosoma brucei encodes only two genes with introns, but all mRNAs are processed by trans-splicing. The presence of three core EJC proteins and a potential BTZ homologue (Rbp25) in trypanosomes has been suggested to adapt of the EJC function to mark trans-spliced mRNAs. We analysed trypanosome EJC components and noticed major differences between eIF4AIII and Magoh/Y14: (i) whilst eIF4AIII is essential, knocking out both Magoh and Y14 elicits only a mild growth phenotype (ii) eIF4AIII localization is mostly nucleolar, while Magoh and Y14 are nucleolar and nucleoplasmic but excluded from the cytoplasm (iii) eIF4AIII associates with nucleolar proteins and the splicing factor CWC22, but not with Y14 or Magoh, while Magoh and Y14 associate with each other, but not with eIF4AIII, CWC22 or nucleolar proteins. Our data argue against the presence of a functional EJC in trypanosomes, but indicate that eIF4AIII adopted non-EJC related, essential functions, while Magoh and Y14 became redundant. Trypanosomes also possess homologues to the NMD proteins UPF1 and UPF2. Depletion of UPF1 causes only a minor reduction in growth and phylogenetic analyses show several independent losses of UPF1 and UPF2, as well as complete loss of UPF3 in the Kinetoplastida group, indicating that UPF1-dependent NMD is not essential. Regardless, we demonstrate that UPF1 depletion restores the mRNA levels of a PTC reporter. Altogether, we show that the almost intron-less trypanosomes are in the process of losing the canonical EJC/NMD pathways: Y14 and Magoh have become redundant and the still-functional UPF1-dependent NMD pathway is not essential.